Peran Komunikasi Politik dalam Menarik Pemilih Pemula pada Pemilihan Presiden 2024 di Kabupaten Bandung - Iqbal Syaefulloh (AT-TAWASUL, 2024)
The 2024 Presidential Election in Indonesia is an important moment that will determine the direction of the country's leadership for the next five years. In Bandung Regency, first-time voters are a very strategic segment in determining election results. This research aims to analyze the role of political communication in attracting the interest of novice voters in Bandung Regency. The methodology used is qualitative with data collection techniques through in-depth interviews. Respondents were selected based on age criteria (17-21 years) and status as first-time voters as many as 43 people with the criteria of living in Bandung Regency as proven by an Identification Card (KTP). All respondents live in Bandung Regency spread across 30 sub-districts. The research results show that effective communication strategies, including the use of social media, involvement in community activities, and conveying relevant messages, have a significant impact on the decisions of first-time voters.